2013
DOI: 10.1182/blood-2012-09-451872
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase 3 trial of thalidomide and prednisone as maintenance therapy after ASCT in patients with MM with a quality-of-life assessment: the National Cancer Institute of Canada Clinicals Trials Group Myeloma 10 Trial

Abstract: • Thalidomide and prednisone maintenance after transplantation improves progressionfree but not overall survival.We conducted a randomized, controlled trial comparing thalidomide-prednisone as maintenance therapy with observation in 332 patients who had undergone autologous stem cell transplantation with melphalan 200 mg/m 2 . The primary end point was overall survival (OS); secondary end points were myeloma-specific progression-free survival, progression-free survival, incidence of venous thromboembolism, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 26 publications
1
87
0
2
Order By: Relevance
“…19 Maintenance with thalidomide-prednisone prolonged PFS, with conflicting OS results. 20,21 This study aims to compare the efficacy and safety of consolidation with CRD versus MEL200-ASCT, followed by maintenance with lenalidomide-prednisone versus lenalidomide alone, in NDMM patients eligible for transplantation.…”
Section: Text Word Count (Max 3000): 2999 Introductionmentioning
confidence: 99%
“…19 Maintenance with thalidomide-prednisone prolonged PFS, with conflicting OS results. 20,21 This study aims to compare the efficacy and safety of consolidation with CRD versus MEL200-ASCT, followed by maintenance with lenalidomide-prednisone versus lenalidomide alone, in NDMM patients eligible for transplantation.…”
Section: Text Word Count (Max 3000): 2999 Introductionmentioning
confidence: 99%
“…Complete response rate has historically correlated poorly with overall survival (Baldini 1991;Riccardi et al, 2003;Durie et al, 2004), and clearly does not take account of quality of life aspects, which are affected by increasingly prolonged myeloma therapy regimens. In early trials, time to progression did correlate with overall survival, but with consolidation treatment this association is no longer seen (Alexanian et al, 2000;Attal et al, 2012;Maiolino et al, 2012;Sonneveld et al, 2012;Stewart et al, 2013). PFS2, the time from first treatment to second relapse, takes account of tumour resistance induced by the first line of treatment, and to date studies have shown it is prolonged in association with PFS (Palumbo et al, 2014b;Tacchetti et al, 2014), but it has not yet been validated as a surrogate for OS, and still takes years of follow up to report mature data.…”
Section: Trial Endpointsmentioning
confidence: 99%
“…A smaller RCT of similar design found a non-significant trend towards increased survival in the thalidomide arm (Maiolino et al, 2012). However an RCT of thalidomide plus prednisolone versus no maintenance found no overall survival difference, and highlighted worse quality of life scores in the maintenance group (Stewart et al, 2013). In all of these trials, adverse events of grade 3 or 4 were much more common in the thalidomide arm, and this is reflected in a thalidomide discontinuation rate of 30% within a year in the study by Spencer et al…”
Section: Maintenancementioning
confidence: 99%
“…To date, only a few studies have analyzed the impact of consolidation or maintenance therapy on QoL. Stewart et al 41 found that the application of thalidomide and prednisone following ASCT had a substantial impact on QoL. Patients reported worse QoL with respect to cognitive function, dyspnea, constipation, thirst, leg swelling, numbness, dry mouth and balance problems.…”
Section: Consolidation Therapymentioning
confidence: 99%